Inclusive guidelines for youth sport stakeholders: A content analysis of US sport national governing body websites - Matthews, A. D. (Michigan State University, University of North Carolina, 2023)
Research emphasizes the organizational responsibilities to foster inclusion in sport (Jeanes et al., 2018; Spaaij et al., 2018). American Sport National Governing Bodies (NGBs) are non-profit, non-governmental organizations that govern activities by setting participation policies, competition rules, as well as monitoring adherence to policies and performance standards. The authoritative relevance of NGBs within the sport system make these governing bodies a vital sample to survey and understand what information is being shared to other stakeholders. The overarching purpose of the current study was to explore the definition and guidelines for fostering inclusion based on information found on US Sport NGB websites.